Electroconvulsive Therapy in a Patient With a Recent Subarachnoid Hemorrhage. Issue 1 (March 2018) - Doddi, Seshagiri Rao; Lotz, Matthew; Regenold, William T.; Adler, Lawrence
Abstract : Abstract: The safety of electroconvulsive therapy (ECT) is improving with advances in anesthesia and ECT technique. There are published case reports of successful treatment of depression in patients who were once considered at high medical risk. Recent cerebral hemorrhage is one of the conditions considered to significantly increase the risk of ECT treatment. Literature search did not indicate any case reports of ECT treatment in patients with recent subarachnoid hemorrhage. We report the successful ECT treatment of depression in an older man who had developed a subarachnoid hemorrhage after a suicide attempt by ingestion of antifreeze.